An incisional hernia containing a gangrenous gallbladder: a case report and review of the literature. Issue 12 (7th December 2022) - Backen, Timbre; Crawley, W Tyler; Bouchard, Travis; Quan, Glenda
Abstract: We present a 76-year-old male who presented to the emergency department with 24 hours of sudden onset, severe abdominal pain. Physical exam and laboratory analysis indicated acute cholecystitis, and a CT scan demonstrated a ventral hernia containing an inflamed gallbladder. This patient was managed operatively with an open cholecystectomy. The ventral hernia was not repaired at the index operation in the setting of frank gallbladder necrosis. The patient recovered well after a short post-operative stay. This report is intended to illustrate an unusual presentation of acute, gangrenous cholecystitis with herniation through the ventral abdominal wall.